Wound healing complications following folded flap palatoplasty in brachycephalic dogs. Issue 12 (7th September 2022) - Khoo, T‐X; Yates, G; Chambers, B; Ng, J
Abstract : Objective: To determine the incidence and characteristics of wound healing complications after folded flap palatoplasty (FFP). Methods: Prospective study of 25 dogs that underwent FFP as a component of corrective multilevel surgery for brachycephalic obstructive airway syndrome. Oropharyngeal re‐examination was conducted after a minimum of 28 days post‐operatively, unless indicated earlier by the onset of clinical signs. Results: Wound healing complications occurred in nine dogs (36%). Minor and major wound complications were diagnosed at a median of 36 days (1.5–51 days) post‐operatively. Eight dogs had major wound complications, four of which showed no associated clinical signs. Two patterns of major wound complications were observed: incisional dehiscence (ID) with caudal retraction of the soft palate mucosa and development of a full‐thickness defect (FTD) in the centre of the soft palate. Revision of the soft palate surgery was performed in five dogs, failing again in one dog with ID. Clinical signs resolved in symptomatic dogs after revision surgery to close FTD. Conclusion: In this study, wound healing complications were common after FFP and were not associated with significant clinical deterioration. Further research is necessary to determine the value and timing of routine post‐operative oropharyngeal examination for assessment of soft palate healing after FFP as well as the indication for and success of approaches to the management of wound healing complications. The two distinct patterns of FFP failure recognised may provide insight into the underlying causes and lead to refinements in folded flap palatoplasty technique.